UPMC Prescription for Wellness: A Quality Improvement Case Study for Supporting Patient Engagement and Health Behavior Change. (May 2018) - Maners, Rebecca J.; Bakow, Eric; Parkinson, Michael D.; Fischer, Gary S.; Camp, Geoffrey R.
Addressing patient health and care behaviors that underlie much of chronic disease continues to challenge providers, medical practices, health systems, and insurers. Improving health and care as described by the Quadruple Aim requires innovation at the front lines of clinical care: the doctor–patient interaction and office practice. This article describes the use of Lean Six Sigma in a quality improvement (QI) effort to design an effective and scalable method for physicians to prescribe health coaching for healthy behaviors in a primary care medical home within a large integrated delivery and financing system. Building on the national Agency for Healthcare Research and Quality and Robert Wood Johnson Foundation–funded Prescription for Health multisite demonstration, this QI case study provides important lessons for transforming patient–physician–practice support systems to better address lifestyle and care management challenges critical to producing better outcomes.